2006
DOI: 10.1182/blood-2005-06-2338
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in bactericidal/permeability-increasing protein influences the risk of developing rapid airflow decline after hematopoietic cell transplantation

Abstract: Innate immunity is involved in the biology of graft versus host disease and common airway diseases. We screened 15 genes in this pathway using a linkage disequilibrium-based approach to identify potential candidate genes that may be involved in the development of airflow obstruction after hematopoietic cell transplantation. Sixty-nine single-nucleotide polymorphisms were selected for assessment in a discovery cohort (n ‫؍‬ 363). Significant associations were validated in a validation cohort (n ‫؍‬ 209). Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Disease risk categories were ranked according to the outcomes we have observed at our Center and have been previously described. 17 Stem cell sources were classified as growth factor-mobilized blood cells, bone marrow, or other, which included cord blood or a combination of bone marrow and mobilized blood cells. Matching between the donor and recipient was determined according to donor-recipient HLA-A, HLA-B, and HLA-DR compatibility.…”
Section: Nested Case-control Studymentioning
confidence: 99%
“…Disease risk categories were ranked according to the outcomes we have observed at our Center and have been previously described. 17 Stem cell sources were classified as growth factor-mobilized blood cells, bone marrow, or other, which included cord blood or a combination of bone marrow and mobilized blood cells. Matching between the donor and recipient was determined according to donor-recipient HLA-A, HLA-B, and HLA-DR compatibility.…”
Section: Nested Case-control Studymentioning
confidence: 99%
“…In humans with bronchiolitis obliterans after allogeneic HSCT, peribronchiolar infiltrate was composed of CD8+T-lymphocytes in one patient [145] and of B-lymphocytes in another patient [146]. Genetic variations in bactericidal/permeability-increasing protein influence the risk of BOS after allogeneic HSCT [147]. Recently, a new murine model for bronchiolitis obliterans after allogeneic HSCT has reproduced bronchiolar abnormalities mimicking human disease [148], and may provide insights into the pathogenesis of bronchiolitis obliterans in humans.…”
Section: Bronchiolitis Obliterans After Lung Transplantationmentioning
confidence: 99%
“…78 Finally, polymorphisms in the bactericidal/permeability-increasing (BPI) gene were recently noted to be significantly associated with the risk of developing bronchiolitis obliterans after HSCT. 79 BPI belongs to a family of lipid transport proteins that have a critical role in the innate immune response to bacterial infection.…”
Section: Polymorphisms In Innate Immunity Genesmentioning
confidence: 99%
“…Evaluation of candidate gene pathways using a linkage disequilibrium approach targeting SNPs in a particular haplotype is a more rational and recently applied method of investigation in this area. 79 Similarly unclear are the importance of SNPs determined to be of significance in individual studies, relative to that of SNPs identified in other studies. In fact, many studies have demonstrated conflicting results.…”
mentioning
confidence: 99%